Pengaruh Akuntabilitas, Transparansi, dan Responsivitas Terhadap Pengelolaan Dana Desa Dalam Upaya Mensejahterakan Masyarakat - Eriana Sri Rahayu; Hestin Sri Widiawati; Sigit Puji Winarko (Jurnal Literasi Akuntansi, 2026)
Purpose: The goal of this study is to look at the factors that affect how village funds are managed, with the aim of helping improve the well-being of the community in Galengdowo Village, Wonosalam Subdistrict, Jombang Regency. It is important to use the principles of good governance in village government, as it helps to properly manage and control the village's funds. But when it comes to managing village funds, there are still a lot of cases where the money is used wrongly, and there's not enough accountability, not much transparency in sharing information, and the government isn't responding properly, all of which can hurt the well-being of the community. Method: This study uses a quantitative method based on cause and effect. Data was gathered by giving out questionnaires and collecting documents using a Likert scale from the people living in Galengdowo Village, and the people chosen for the study were selected through purposive sampling. Classical assumption tests, moderating regression analysis, multiple linear regression tests, R squared coefficient of determination tests, and hypothesis tests were used in the data analysis. The study included everyone living in Galengdowo Village, and there were a total of 3,868 people in the village. Sampling was done using purposive sampling; out of a total population of 3,868 people, 2,369 were chosen. The sample selection used the Slovin formula to figure out how many people were needed, and the smallest number of people required was 96. Finding: The study shows that, to some extent, Accountability doesn't greatly influence how Village Funds are managed, but Transparency and Responsiveness do have a strong impact. At the same time, Accountability, Transparency, and Responsiveness play a big role in how Village Funds are managed. The moderation test results show that Community Well-being affects how Accountability and Responsiveness influence Village Fund Management, but it does not affect how Transparency influences Village Fund Management.. Novelty: The novelty of this study lies in the Responsiveness variable and the inclusion of an intervening variable used to strengthen the dependent and independent variables